Driving Motivation in Irish Language Learning: An analysis of variation in post-primary pupil attitudes to Irish in the Growing Up in Ireland study - Emily Barnes; Joe Condon; Ann Devitt; Noel Ó Murchadha (Teanga: The Journal of the Irish Association for Applied Linguistics)
This study provides a novel perspective on minority language motivation using Situated Expectancy Value Theory to examine the attitudes of post-primary students in Ireland to learning the national minority language, Irish.  The paper uses data from Growing Up in Ireland, the national longitudinal study of the well-being and development of children and young people in Ireland, to explore factors influencing young people’s motivation in relation to learning the Irish language, controlling for overall engagement with schooling.  Using data from over 7000 students surveyed at two time points, the findings suggest that young people’s attitudes to learning Irish remain relatively stable over time, from primary to post-primary.  The analysis demonstrates that the language of schooling (English or Irish) is the factor which relates most closely to attitudes to Irish.  Furthermore, contextual classroom factors were of critical importance in sustaining motivation in relation to the language.  In particular, a more student-centred teaching style and higher positive and lower negative interactions with teachers were associated with more positive perceptions of Irish as less difficult and more interesting.  This paper informs key policy priorities to support the maintenance of the Irish language by optimising interest-enjoyment value and minimising the challenges associated with learning Irish for young people in post-primary education.